2012
DOI: 10.1016/j.compscitech.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Statistical modeling of in-plane permeability of non-woven random fibrous reinforcement

Abstract: International audienceA methodology has been proposed for statistical characterization of transport behavior of a typical random fibrous medium, i.e. the Chopped Strand Mat (CSM). For any given digital images of fabric sample, statistical description of the random microstructure is employed to evaluate the permeability field, in the framework of the statistical continuum approach. By choosing suitable sampling strategy, the evaluated permeability field can be used to predict the realistic fluctuation in the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…These families of distributions (GEV, power law, pareto, lognormal) have been found to be useful for stochastic modelling [32,33,34,35,36] when inputs such as permeability follow heavy-tailed distributions. However, the use of 210 mixture model is more complex than GEV.…”
Section: Correlation Between Tortuosity Porosity and Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…These families of distributions (GEV, power law, pareto, lognormal) have been found to be useful for stochastic modelling [32,33,34,35,36] when inputs such as permeability follow heavy-tailed distributions. However, the use of 210 mixture model is more complex than GEV.…”
Section: Correlation Between Tortuosity Porosity and Permeabilitymentioning
confidence: 99%
“…where D h = 4/d [11] is the hydraulic diameter and ψ CK is the Kozeny factor. Substituting the expression of the hydraulic diameter in equation (15) and…”
Section: Correlation Between Tortuosity Porosity and Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical modeling of permeability variations [5] or stochastic simulation of resin flow [6] has also been studied to further improve optimization of the processing conditions. However, it is almost impossible to control and optimize many factors involved in an LCM process prior to manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data from those studies were used in the models of textile reinforcements with variability in the geometry and used for prediction of probability of draping outcomes, 8 distribution of mechanical properties 12 and permeability. 7,[16][17][18][19][20] In particular, it was demonstrated that the mould fill time can be several times longer than the fill time in the deterministic case. 18 The geometry of a dry reinforcement can be described by a model where tow position, tow width and other details are described by a set of random variables, which may be mutually independent or can be correlated.…”
Section: Introductionmentioning
confidence: 99%